Occurrence of Prehnite, Pumpellyite and Garnet in Biotite from Granitic Rocks of the Canadian Appalachians: A Mineral Chemistry Study Using Electron Microprobe - A.A. T. Shabani (Journal of Sciences, Islamic Republic of Iran)
A particular feature of biotite grains from some of the Canadian Appalachian granitic rocks is the presence of lenses of Ca-Al silicates developed along cleavage planes. These from the more to less common are prehnite, pumpellyite and grandite garnet, an intermediate composition between andradite and grossular. Rarely all three minerals can be observed together in one single biotite grain. Microprobe analyses show that Al2O3 contents of prehnite vary from 17.52 to 24.55 and Fe2O3 from 2.38 to 8.88 wt. %, which can be reflected in a substantial and variable substitution of Fe for Al. Furthermore, a fairly positive correlation of MnO values of both prehnite and host biotite may indicate the role of biotite replacement by prehnite. Fe2O3 content in nine analyzed pumpellyite samples varies between 10 and 23 wt%. Fe2O3 contents of more than 10 wt% in pumpellyite are indicative of zeolite and prehnite-pumpellyite facies conditions.